(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2012)
When the returns generated by the assets of a company (return on assets) is greater than the cost of the resources provided by third parties (liabilities), an effect of financial leverage that allows returns for owners of the company (heritage ) are higher as you grow that level of indebtedness. However, as the calculation of profitability is subject to different levels of utility and the calculation of the latter is not considered the cost of capital to shareholders, these indicators do not actually receive if the company is generating value or not. The methodology of the Economic Value-Added -EVA- is a technique that may resolve this problem, because it compares the performance that is capable of creating a company with the cost of the resources that allowed him to achieve that outcome and is based on the resources employed by a business must produce a return higher than their cost, if not, it’s best to move the resources used for other activities.